Tariff Aspects of a Federal Union - de Beers, John S. (Quarterly Journal of Economics, 1941)
I. Introduction: federal unions and customs unions, 49. — II. Long-run economic consequences, 51. — Revenue tariff, 54. — Moderate protection, 61. — Extreme protection, 64. — Tentative conclusions: conditions making for economic gain by country granting preferential tariff reductions, 66; economic benefits may be reduced or cancelled by policy of self-sufficiency, 70. — III. Transitional economic problems: Streit's proposal, 71; Meade's suggestions, 74; Salter's plan, 75; regional groups, 76; formula to assure permanent gain, 79. — IV. The most-favored nation clause, 80. — V. The tariff authority, 88. — VI. Conclusions, 91.